To determine which equations have no solutions, let's analyze each equation step by step.
-
Equation: \(7x + 3 - 4x = 3(x + 1)\)
- Simplify left side: \(3x + 3 = 3(x + 1)\)
- Expanding right side: \(3x + 3 = 3x + 3\)
- This is true for all values of \(x\). Thus, it has infinitely many solutions.
-
Equation: \(2(x + 2) = 2x + 2\)
- Expanding left side: \(2x + 4 = 2x + 2\)
- Subtracting \(2x\) from both sides: \(4 = 2\)
- This is a false statement, meaning this equation has no solutions.
-
Equation: \(5x + 5 = 5(2x + 2)\)
- Expanding right side: \(5x + 5 = 10x + 10\)
- Rearranging: \(5 = 5x + 10\) → \(5 - 10 = 5x\) → \(-5 = 5x\) → \(x = -1\)
- This equation has a solution.
-
Equation: \(6(x + 8) = 6x + 5\)
- Expanding left side: \(6x + 48 = 6x + 5\)
- Subtracting \(6x\) from both sides: \(48 = 5\)
- This is a false statement, meaning this equation has no solutions.
Summary
The equations with no solutions are:
- \(2(x + 2) = 2x + 2\)
- \(6(x + 8) = 6x + 5\)
Thus, the final answers are:
- \(2(x + 2) = 2x + 2\)
- \(6(x + 8) = 6x + 5\)